2008
DOI: 10.1007/s12020-008-9051-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 in fat tissue

Abstract: The literature describing vitamin D content of fat tissue is extremely limited. We conducted a pilot study that measured the concentrations of vitamin D(3) in the fat tissue and serum of obese adults. These measurements were performed using a new liquid chromatography mass spectrometry (LC/MS) method. The objectives of this study were: to measure and report the vitamin D(3) concentration in serum and subcutaneous fat samples from obese individuals and to examine the association of vitamin D(3) in fat with vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
239
4
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(286 citation statements)
references
References 15 publications
25
239
4
18
Order By: Relevance
“…Similar findings were reported by others after diet and/or exerciseinduced weight loss. 9,10,12 These findings are in agreement with the hypothesis that VD is being stored in the AT 24,26 and confirm previous data on how plasma 25OHD depends on the volume of distribution. 23 The increase in 25OHD fits very well with the observed increased expression of the degrading enzyme, the 24-hydroxylase CYP24A1, as CYP24A1 expression is induced by 1,25-OH 2 D. 36,37 As CYP24A1 degrades both 25OHD and 1,25(OH) 2 D, these findings suggest a higher turnover of both 25OHD and 1,25(OH) 2 D following weight loss.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar findings were reported by others after diet and/or exerciseinduced weight loss. 9,10,12 These findings are in agreement with the hypothesis that VD is being stored in the AT 24,26 and confirm previous data on how plasma 25OHD depends on the volume of distribution. 23 The increase in 25OHD fits very well with the observed increased expression of the degrading enzyme, the 24-hydroxylase CYP24A1, as CYP24A1 expression is induced by 1,25-OH 2 D. 36,37 As CYP24A1 degrades both 25OHD and 1,25(OH) 2 D, these findings suggest a higher turnover of both 25OHD and 1,25(OH) 2 D following weight loss.…”
Section: Discussionsupporting
confidence: 91%
“…[24][25][26][27] 25-Hydroxyvitamin D is the dominant circulating form of VD, and the best indicator of VD status. 8 The formation, activation and catabolism of 25OHD is a complex process, which involves the mitochondrial and microsomal cytochrome P450 enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Even in individuals who are not obese, body size and adiposity are inversely associated with blood 25(OH)D concentrations (37,49). It has been shown that concentrations of 25(OH)D 3 in biopsies of subcutaneous fat tissue from obese men and women were inversely related to the degree of overweight and positively to the concentrations of circulating 25(OH)D 3 (50). The positive association of serum and subcutaneous fat tissue vitamin D 3 concentrations is compatible with the long-standing concept that adipose tissue is a storage site for vitamin D (51).…”
Section: Discussionmentioning
confidence: 99%
“…2 In India more than 90% of apparently healthy Indians have subnormal 25(OH) D levels. [3][4][5][6] The endocrine society suggests that serum levels of 25 [OH] D less than 20 ng/ml as deficiency and levels between 21-29 ng/mL as insufficiency, while levels of 25[OH] D above 30 ng/mL are optimum levels of the vitamin.…”
Section: Introductionmentioning
confidence: 99%